Exploring the Relationship Between Corporate Governance and Financial Performance in Emerging Economies - Rina Adelia; Budi Santoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article analyzes how corporate governance practices influence financial performance in companies within emerging economies. Using data from firms in Asia and Africa, the research examines the impact of board composition, audit quality, and transparency on profitability and shareholder value. Findings indicate that robust corporate governance practices contribute to better financial outcomes, enhancing the stability and attractiveness of companies in emerging markets.